KEPATUHAN KONSUMSI TABLET FE PADA IBU HAMIL: APAKAH FAKTOR REINFORCING BERPENGARUH? - Herawati, Nurul; Kartikasari, M. Nur Dewi; Triswanti, Triswanti; Sendra, Eny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Adherence to iron tablet consumption among pregnant women is one of the key factors determining the success of preventing and managing anemia during pregnancy. According to a preliminary survey, the Sadabuan Health Center in Padangsidimpuan City recorded 714 pregnant women registered in health services in 2024. Of this number, 53 pregnant women were diagnosed with anemia. The purpose of this study was to determine the relationship between reinforcing factors and compliance with iron tablet consumption among pregnant women. The study design used in this research was cross-sectional. The study was conducted in Losungbaru Village in January 2024. The study population consisted of all pregnant women in Losungbatu Village, totaling 149 pregnant women. The study sample consisted of 60 respondents. The sampling technique used was simple random sampling. The research instrument used was a questionnaire. Data analysis was conducted using univariate and bivariate methods. The results of the study indicated a significant relationship between spousal support (p-value: 0.001) and adherence to iron tablet consumption. Health workers, especially those at community health centers, are advised to continue providing information through individual counseling during home visits or group counseling during posyandu (integrated health service post) sessions. The information received will have a positive impact on health promotion in the future and provide counseling to pregnant women about iron tablets, their effects, and their benefits for pregnant women.Keywords: Spousal Support, Pregnant Women, Compliance.